ANALISIS PENGARUH TEMPERATUR MEDIA PENDINGIN PROSES PENGELASAN SMAW TERHADAP NILAI KEKERASAN DAN PADA BAJA KARBON SEDANG - Jefri Aldo; Rijal Surya Rahmany (Mechanical Engineering Department, Faculty of Engineering, Universitas Lambung Mangkurat, 2022)
This research aims to analyze the effect of the comparison of the temperature of the cooling medium used in the cooling process of medium carbon steel welded using a SMAW welding machine to the hardness values. The cooling medium used is SAE 5W 30 oil with different temperatures of 80°C, 90°C, and 100°C. The research was carried out by using the method of welding on medium carbon steel and cooling it with oil media at different temperatures, then testing the Vickers hardness with a load of 40 kgf. Researchers used oil cooling media without heating, and room temperature as a differentiator, as a result, through this research, generally different results were obtained, namely the hardness number of non-media materials 103, 584972 VHN, oil without heating 108, 127134 VHN, oil 80°C 108 , 36668 VHN, 90°C 110 oil, 5910479 VHN, 100°C 101 oil, 4692936 VHN.